The Effectiveness of the Reading Corner in the Independent Curriculum Program to Enhance Literacy Culture for Early Childhood at RA Islamic Mahardika - Syahputri, Desi; Ritonga, Ristra Sandra (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the effectiveness of the reading corner program in improving literacy culture among early childhood students at RA Islamic Mahardika under the Independent Curriculum framework. Literacy culture plays a crucial role in shaping children's reading and writing skills from an early age. The research employs a quasi-experimental method with a one-group pretest-posttest design involving 10 children as the sample. Data collection was conducted through observation and documentation of children's voluntary visits to the reading corner. Statistical analysis using SPSS version 26 includes the Shapiro-Wilk normality test, Paired Sample t-Test, and Cohen’s d effect size measurement. The results indicate a significant increase in literacy culture after implementing the reading corner program, as demonstrated by the increase in children's reading, writing, and storytelling engagement. The Paired Sample t-Test yielded a p-value of 0.038 (p < 0.05), confirming a statistically significant improvement. Additionally, the effect size of 1.64 (Cohen’s d) suggests a strong impact of the program. These findings highlight the importance of structured literacy interventions in early childhood education, reinforcing the necessity of integrating engaging literacy activities within the Independent Curriculum framework.